Detection of temporal structures in basketball - Pic Aguilar, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2017)
Summarizing a basketball game to effectiveness at launch, offensive rebounds and / or defensive, among other indicators; it can be risky, based on the relational complexity existing in a basketball game. However, traditionally; it has been investigated success in basketball on data without a time reference. Temporary identification and behavioral regularities can be challenging research to help realize training planning and strategic optimization of equipment. The temporary record of successes and failures in launching among other indicators, can provide an unavoidable time dependence, invisible to an apparent look. This is the primary purpose of work to optimize strategies implemented in matches and thus the realization of greener routines according to the demands of the parties in training. It was an observational methodology used a nomothetic, punctual and multidimensional design for the registration of motor behavior organized around a mixed system of registration ’had oc’. For the analysis of the temporal dimension of the records it was used the technique T-patterns (Magnusson, 2000), thus enabling the identification of motor asymmetries. The results show most relevant temporal and strategic regularities. The identification of strategic pathways teams reveal functional accommodation between the teams.